Secondary Anetoderma Overlying Multiple Pilomatrixomas: A Case Report - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2009)
Pilomatrixoma is a benign skin tumour originating from hair matrix cells. It usually presents as a solitary nodule or cyst. Multiple lesions are rare and are familial in majority of cases. Anetodermic changes overlying pilomatrixomas have rarely been described. We report here an 18-year old girl with six pilomatrixomas. None of her family members had similar lesions. Three of the lesions which were located on the back and arm showed features of secondary anetoderma. (Turkderm 2009, 43: 116-8)
Keywords: Multiple pilomatrixoma; anetoderma; PILOMATRICOMAS